Inflating bacterial cells by increased protein synthesis. Issue 10 (October 2015) - Basan, Markus; Zhu, Manlu; Dai, Xiongfeng; Warren, Mya; Sévin, Daniel; Wang, Yi‐Ping; Hwa, Terence
Abstract: Understanding how the homeostasis of cellular size and composition is accomplished by different organisms is an outstanding challenge in biology. For exponentially growing Escherichia coli cells, it is long known that the size of cells exhibits a strong positive relation with their growth rates in different nutrient conditions. Here, we characterized cell sizes in a set of orthogonal growth limitations. We report that cell size and mass exhibit positive or negative dependences with growth rate depending on the growth limitation applied. In particular, synthesizing large amounts of "useless" proteins led to an inversion of the canonical, positive relation, with slow growing cells enlarged 7‐ to 8‐fold compared to cells growing at similar rates under nutrient limitation. Strikingly, this increase in cell size was accompanied by a 3‐ to 4‐fold increase in cellular DNA content at slow growth, reaching up to an amount equivalent to 8 chromosomes per cell. Despite drastic changes in cell mass and macromolecular composition, cellular dry mass density remained constant. Our findings reveal an important role of protein synthesis in cell division control. Synopsis: Protein overexpression inverts the well‐known positive relation of cell size and DNA content with growth rate under nutrient limitation, resulting in huge, slowly growing cells with high DNA content, but with remarkably constant cellular dry mass density. Protein overexpression leads to an inverted growth rate dependence of cell size, with slow growing cells being even larger than the fastest growing wild‐type cells cultured in rich media. Decoupled from growth rate, changes in cell size are accompanied by comparable changes in cellular DNA content. Despite profound changes in cell size and macromolecular composition, cellular dry mass density remains remarkably constant, as protein overexpression does not result in molecular crowding. Abstract : Protein overexpression inverts the well‐known positive relation of cell size and DNA content with growth rate under nutrient limitation, resulting in huge, slowly growing cells with high DNA content, but with remarkably constant cellular dry mass density.